Ultrasonography Study of Median Nerve in Patients of Carpal Tunnel Syndrome and its Correlation with Nerve Conduction Study in A Tertiary Care Institute of Eastern India - Payal Agrawal; Madhumita Debata; Bhabani Prasad Panda; Sasmita Parida (JK Science)
Introduction: Carpal tunnel syndrome (CTS) involves symptoms from median nerve compression in carpal tunnel. Diagnosis relies on symptoms, signs and median nerve conduction study (NCS). High resolution ultrasonography (HRUS) and MRI are non-invasive methods for assessing the median nerve, with HRUS being better for dynamic examinations. Aim & Objectives: This study aims to evaluate diagnostic utility of B-mode ultrasonography and Doppler study in clinically diagnosed CTS and to assess its specificity and sensitivity for CTS diagnosis. Material and Methods: HRUS of median nerve was performed on 130 clinically diagnosed CTS patients. Sonomorphologic features and intraneural vascularity were assessed and USG parameters were correlated with NCS to determine accuracy and reliability. Results: Nerve swelling had the highest sensitivity (80.3%) and accuracy (80.67%). Difference in cross-sectional area at tunnel inlet and pronator quadratus showed high accuracy (98.67%) and 100% sensitivity compared to NCS. Intraneural vascularity using Doppler had 100% specificity and PPV for CTS. Conclusion: Among USG criteria, nerve swelling provided best detect ability of CTS with tunnel inlet being most accurate location for increase in area of median nerve. Differences in CSA at level of tunnel inlet and pronator quadratus showed comparable accuracy to NCS. Intraneural vascularity was highly specific for CTS. Hence ultrasonography can be an alternative diagnostic modality for CTS.